Experimental and Numerical Analysis of Effect of Cooling Rate on Thermal-Microstructural Response of Spheroidal Graphite Cast Iron Solidification - Schulz-Eglin, B; Cruchaga-Ssa., M (Maney Publishing, 2014)
This work presents an experimental and numerical study of the solidification process of an eutectic spheroidal graphite cast iron (SGI). The effect of the cooling rate on the thermal-microstructural response is particularly analysed. To this end, experiments as well as numerical simulations were carried out. The experiments consisted in a solidification test in a wedge-like casting such that different cooling rates were measured at specific positions along the part. A metallographic analysis was also performed in five locations of the sample with the aim of obtaining the number and size of graphite nodules at the end of the process. The numerical simulations were made using multinodular based and uninodular based models. These two models predicted similar results in terms of cooling curves and nodule counts. Besides, good experimental-numerical agreements were obtained for both the cooling curves and the graphite nodule counts. © 2014 W. S. Maney & Son Ltd.